الإصلاح السياسي عند مفسري القرآن الكريم في النصف الأول من القرن العشرين : رشيد رضا وطنطاوي جوهري نموذجا - محيي الدين، حازم زكريا (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2007)
In this dissertation, the researcher has tried to study and analyze in general the reformist discourse, and the political discourse in particular as it is embodied in the writings of the exegetes of the first half of the twentieth century. This is done in the main in an attempt to answer the question of how those exegetes responded and interacted with the modern political ideas, and the historic transformations, which the Islamic World had witnessed during that era. This is being the case based on the conviction that the interaction of the exegetes with the spirit and thought of their era, and their use of the Qur’ān to find practical solutions to the major problems facing the exegetes is one of the major tasks of the exegetes. To achieve this, the researcher has used the case study approach. From the exegetes of that era he has chosen Rashīd Ridā (d.1935), the author of Al- Manār Tafsīr, and Tantāwī Jawharī (d.1940), the author of Al- Jawāhir Tafsīr. These two intellectuals have been used as representatives of the exegetes during the first half of the twentieth century. The researcher has used the contextual analysis approach in understanding the political discourse of these two intellectuals, particularly the way they approached the two core concepts of the authority and political values, which have occupied the center stage of their political thought. In addition, the researcher has utilized the historical method in exploring the arguments of both writers in their discussions about the Ottoman Caliphate, the issue of Western colonization, and the Palestinian issue. Whenever and wherever warranted, the researcher has resorted to the critical method. The major finding of this study is that both Ridā and Jawharī have utilized their respective exegesis as a platform to propagate political refom in the light of the values and the objectives of the Qur’an. This testifies that both writers have symbolized the model of reformist exegete who shoulders his historic mission while engaging in their exegeses. However, on balance, the two exegetes have not succeeded in creating a theoretical method for the interaction between the Qur’an and its interpretation on the one hand and facts of reality and history on the other hand. This has resulted in some shortcomings in the applied aspect of their exegeses.